Kedudukan Legitieme Portie dalam Hal Pemberian Hibah Wasiat Berdasarkan Hukum Waris Burgerlijk Wetboek - Willliam Setiawan Marthianus (Notaire, 2019)
Will is one of the ways to inheritance. According to article 875 BW, a testament or last will is a deed, containing a statement of an individual’s wishes and intents to take effect following his death, and which deed can be revolved. Testament or last will can be made while the testator is still alive, but the implementation is only do able when the testator passed away. Testamentary offers an additional option to testator while he/she is still alive the inheritance can be distributed to the beneficiary or heir, according to article 957 BW, testamentary gifting is a special testament, under which the testator bestows onto one or more person his properties of a certain kind, for example, all of his properties, movable or immovable, or the usufruct rights over entire part of his estate. It is special testament because it can pass distributed the inheritance on special occasion such as when the amount of successor is more than one, it can give special and certain kind of properties, such as movable or immovable properties, and usufruct rights. Problem arise when testamentary gifting is given to the successor without obeying the provisions according to legitimate portie. This condition is contrary with article 913 BW which states that The Legitimate portion or the legal share of the inheritance is that portion of the estate which the lawful heirs in a direct line are entitled to and which the testator is not entitled to dispose of as a gift during his life time or by last will.